Rhodium(III)‐Catalyzed Dehydrogenative Annulation of 2‐Arylindazoles with Cyclic Enones. Issue 21 (8th June 2021) - Chary Devulapally, Yogananda; Ittamalla, Chaitanya; Balasubramanian, S.; Venkata Subba Reddy, Basireddy
Abstract: An oxidative annulation of 2‐arylindazoles with cyclic enoneshas was developed using Rh(III)/Cu(OAc)2 catalytic system for the first time to produce 3, 4‐dihydroindazolo[2, 3‐ f ]phenanthridin‐1(2 H )‐one derivatives in good yields with high selectivity. When AgSbF6 was used instead of Cu(OAc)2, the corresponding uncyclized products, 3‐(2‐(2H‐indazol‐2‐yl)phenyl)cyclohexan‐1‐one scaffolds were formed exclusively. The reaction proceeds through a sequential conjugate addition of ortho ‐C–H bond of aryl group followed by an oxidative annulation of indazole ring to generate fused polycyclic scaffolds. Abstract : An oxidative annulation of 2‐arylindazoles with cyclic enoneshas was developed using Rh(III)/Cu(OAc)2 catalytic system for the first time to produce 3, 4‐dihydroindazolo[2, 3‐ f ]phenanthridin‐1(2 H )‐one derivatives in good yields with high selectivity. When AgSbF6 was used instead of Cu(OAc)2, the corresponding uncyclized products, 3‐(2‐(2H‐indazol‐2‐yl)phenyl)cyclohexan‐1‐one scaffolds were formed exclusively.